Prostaglandin D2 effects and DP1/DP2 receptor distribution in guinea pig urinary bladder out‐flow region. Issue 2 (23rd September 2016) - Guan, Na N.; Svennersten, Karl; de Verdier, Petra J.; Wiklund, N. Peter; Gustafsson, Lars E.
Abstract: The proximal urethra and urinary bladder trigone play important roles in continence. We have previously shown that PGD2 is released from guinea pig bladder urothelium/suburothelium and can inhibit detrusor contractile responses. We presently wished to investigate PGD2 actions in guinea pig out‐flow region and the distribution of DP1 /DP2 receptors. The effects of PGD2 on urothelium‐intact trigone and proximal urethra contractility were studied in organ bath experiments. Expression of DP1 /DP2 receptor proteins was analysed by western blot. Immunohistochemistry was used to identify distribution of DP1 /DP2 receptors. PGD2 in a dose‐dependent manner inhibited trigone contractions induced by electrical field stimulation (EFS) and inhibited spontaneous contractions of the proximal urethra. PGD2 was equally (trigone) or slightly less potent (urethra) compared with PGE2 . Expression of DP1 and DP2 receptors was found in male guinea pig bladder trigone, neck and proximal urethra. In the trigone and proximal urethra, DP1 receptors were found on the membrane of smooth muscle cells and weak immunoreactivty was observed in the urothelium. DP2 receptors were distributed more widespread, weakly and evenly in the urothelium and smooth muscles. Inhibitory effects by PGD2 on motor activity of guinea pig trigone and proximal urethra are consistent with finding DP1 and DP2 receptors located in the urothelium and smooth muscle cells of the trigone and proximal urethra, and PGD2 may therefore be a modulator of the bladder out‐flow region, possibly having a function in regulation of micturition and a role in overactive bladder syndrome.